2010
DOI: 10.1002/pmic.200900178
|View full text |Cite
|
Sign up to set email alerts
|

Functional proteomic and structural insights into molecular targets related to the growth inhibitory effect of tanshinone IIA on HeLa cells

Abstract: Certain antitumor agents have recently been extracted from the roots of Salvia miltiorrhiza Bunge. The diterpene derivative, tanshinone IIA, possesses cytotoxic activity against several human carcinoma cell lines. It also inhibits invasion and metastasis of cancer cells. In the present study, we isolated tanshinone IIA from S. miltiorrhiza, and it exhibited strong growth inhibition against human cervical cancer cells in dose- and time-dependent manners with a 50% cell growth inhibition value of 2.5 microg/mL (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 47 publications
0
68
0
Order By: Relevance
“…The effects of SBEE on cell cycle were evaluated by flow cytometry (Pan et al, 2010). HSC-T6 cells were treated with SBEE with the indicated concentrations for 24 h and harvested by centrifugation at 750 × g for 5 min at room temperature.…”
Section: Flow Cytometric Analysismentioning
confidence: 99%
“…The effects of SBEE on cell cycle were evaluated by flow cytometry (Pan et al, 2010). HSC-T6 cells were treated with SBEE with the indicated concentrations for 24 h and harvested by centrifugation at 750 × g for 5 min at room temperature.…”
Section: Flow Cytometric Analysismentioning
confidence: 99%
“…Recent researches have shown that TIIA is a natural anti-tumor drug, which has cytotoxic effect on many tumors and inhibits the invasion and migration of cancer cells. For example, TIIA could inhibit the cell growth of reproductive system tumors, such as breast cancer (Su and Lin, 2008;Lu et al, 2009), cervical cancer (Pan et al, 2010), ovarian cancer (Jiao and Wen, 2011) and prostatic carcinoma (Won et al, 2010); TIIA disrupts the membrane potential of mitochondria, induces apoptosis and reduces the adhesion and invasion of cells in acute promyelocytic leukemia. However, few studies have been reported to investigate the effect of TIIA on gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Tanshinones, abietane-type norditerpenoid quinones, have been shown to exhibit diverse pharmacological activities, including antibacterial (Lee et al, 1999), antioxidant (Cao et al, 1996), antidiabetes (Kim et al, 2007), anti-cancer (Wang et al, 2005; 2009; Chiu and Su, 2010;Pan et al, 2010) and anti-inflammatory (Jang et al, 2003) activity. Since the roots of P. abrotanoides contain therapeutically applicable tanshinones, the mass cultivation of roots in vitro could be an effective technique for the large-scale production of these valuable secondary metabolites.…”
Section: Introductionmentioning
confidence: 97%